Foetal macrosomia: risk factors, maternal and foetal outcomes in N'Djamena Mother and Child Hospital, Chad - Gabkika Bray Madoue; Souan Nguele Sile; Foumsou Lhagadang (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2018)
Background: Macrosomia is a birth weight above the 90th percentile corrected for gestational age and sex, or birth weight of 4000-4500 g. Objective: To determine the incidence of foetal macrosomia and macrosomia-associated maternal and perinatal morbidity and mortality. Patients and method: This was a cross-sectional study covering a period of six months, from January to June 2016 in N'Djamena Mother and Child Hospital, Chad. The sample consisted of two groups: mothers who gave birth to macrosomic babies (the study group) and an equal number of mothers who gave birth to normosomic babies (the control group). Results: Out of a total of 5,284 deliveries, 403 babies weighed 4.0 kg or more giving an incidence of macrosomia of 7.6%. The mean maternal age and mean birth parity of the study group were significantly greater than in the control group. There were significantly more mothers with a previous history of macrosomia in the study group than in the control group. Ninety three babies (23.1%) in the study group were delivered by Caesarean Section, and 76.9% by vaginal delivery. The commonest maternal complications were: postpartum haemorrhage (15.9%), prolonged labour (13.9%) and perineal laceration (4.4%). There were significantly more babies with a poor Apgar score in the first and the fifth minute in the study group than in the control group (P= 0.0009). Other complications among the macrosomic babies were: shoulder dystocia (1.3%), stillbirths (0.7%) and hypoglycaemia (8.4%). Conclusion: Macrosomic neonates are more often delivered by Caesarean Section than normosomic babies. There is a clear need during prenatal care and delivery to minimise maternal and perinatal complications. Keys words: Caesarean Section, foetal macrosomia, complications, N'Djamena Mother and Child Hospital